Multifactorial structure of cognitive assessment tests in the UK Biobank: A combined exploratory factor and structural equation modeling analyses - Ciobanu, Liliana G.; Stankov, Lazar; Ahmed, Muktar; Heathcote, Andrew; Clark, Scott Richard; Aidman, Eugene (Frontiers in Psychology, 2023)
The UK Biobank cognitive assessment data has been a significant resource for researchers looking to investigate predictors and modifiers of cognitive abilities and associated health outcomes in the general population. Given the diverse nature of this data, researchers use different approaches – from the use of a single test to composing the general intelligence score, g, across the tests. We argue that both approaches are suboptimal - one being too specific and the other one too general – and suggest a novel multifactorial solution to represent cognitive abilities. Using a combined Exploratory Factor (EFA) and Exploratory Structural Equation Modelling Analyses (ESEM) we developed a three-factor model to characterise an underlying structure of nine cognitive tests selected from the UK Biobank using a Cattell-Horn-Carroll framework. We first estimated a series of probable factor solutions using the maximum likelihood method of extraction. The best solution for the EFA-defined factor structure was then tested using the ESEM approach with the aim of confirming or disconfirming the decisions made. We determined that a three-factor model fits the UK Biobank cognitive assessment data best. Two of the three factors can be assigned to fluid reasoning (Gf) with a clear distinction between visuospatial reasoning and verbal-analytical reasoning. The third factor was identified as a processing speed (Gs) factor. This study characterises cognitive assessment data in the UK Biobank and delivers an alternative view on its underlying structure, suggesting that the three-factor model provides a more granular solution than g that can further be applied to study different facets of cognitive functioning in relation to health outcomes and to further progress examination of its biological underpinnings.